2011
DOI: 10.3892/ol.2011.516
|View full text |Cite
|
Sign up to set email alerts
|

Adjuvant chemotherapy following concurrent chemoradiotherapy for uterine cervical cancer with lymphadenopathy

Abstract: Abstract. The present study aimed to retrospectively evaluate the efficacy and toxicities of adjuvant chemotherapy with paclitaxel and carboplatin (TC) following concurrent cisplatin-based chemoradiation (CCRT) in patients with cervical cancer with lymphadenopathy (N1). A total of 37 patients with FIGO stage IB2-IVA cervical carcinoma with N1 (median age 57 years, range 31-74 years) were enrolled. External beam radiation therapy was followed by high-dose-rate brachytherapy. In cases of suspected para-aortic ly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
27
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 21 publications
2
27
0
Order By: Relevance
“…Pelvic lymph node metastasis has long been established as the most important prognostic factor in cervical cancers. However, common iliac and para‐aortic lymph node metastases in cervical cancer have been reported to be associated with markedly poor survival than other pelvic lymph node metastases . The prognoses of the patients with common iliac and para‐aortic lymph node metastasis were comparable after radical hysterectomy .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pelvic lymph node metastasis has long been established as the most important prognostic factor in cervical cancers. However, common iliac and para‐aortic lymph node metastases in cervical cancer have been reported to be associated with markedly poor survival than other pelvic lymph node metastases . The prognoses of the patients with common iliac and para‐aortic lymph node metastasis were comparable after radical hysterectomy .…”
Section: Resultsmentioning
confidence: 99%
“…However, common iliac and para-aortic lymph node metastases in cervical cancer have been reported to be associated with markedly poor survival than other pelvic lymph node metastases. 27,28 The prognoses of the patients with common iliac and para-aortic lymph node metastasis were comparable after radical hysterectomy. 29 Therefore, further analysis was performed to investigate the association between MMP-7 and MMP-9 expression and positive common iliac artery and para-aortic lymph nodes.…”
Section: Association Of Mmp-7 and Mmp-9 Expression With Postoperativementioning
confidence: 97%
“…However, several issues remain unresolved; for example, the selection of diagnostic tools for pretreatment assessment, the role of prophylactic extended-field RT (1,2), and the benefit of adjuvant chemotherapy (3,4).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, patients with PA metastasis 255 were excluded from the study and a specific analysis concluded 256 this treatment was not cost-effective, due to increased financial 257 burden and toxicity [26]. In a retrospective evaluation of patients 258 with PA spread, paclitaxel and carboplatin-based adjuvant 259 chemotherapy led to better outcomes than CRT alone, despite 260 increased toxicity [27]. Neoadjuvant chemotherapy has also been 261 evaluated, with high response rates [28][29][30][31][32].…”
mentioning
confidence: 99%